The quest for organizational flexibility: driving changes in business processes through the identification of relevant context. Issue 4 (4th July 2016) - Anastassiu, Monica; Santoro, Flavia Maria; Recker, Jan; Rosemann, Michael
Abstract : Purpose: This paper proposes a method for identifying business process-relevant contextual information that is likely to impact on the process goal. The ORGANON method describes a semi-structured procedural guide alongside with a set of criteria and a matrix for analyzing ontological transactions, which can be used to identify which context information can be considered relevant to a business process. Design/methodology/approach: We report on an evaluation of the ORGANON method through a case study conducted in an organization that works in the social security domain. Findings: The results provide evidences of the feasibility of the method application in this scenario. Originality/value: Our research contributes to the literature on business processes flexibility, specifically through a proposal for context identification that can be extended to current techniques for business process modeling and in turn forms the basis for existing approaches for making business processes more flexible. The work has implications for the strategic management of organizations, by suggesting a method that provides informational support to decision-makers about when, where and why business processes need to be adapted.